Commander in chief - Greaney, Mark (G.P. Putnam's Sons, 2015)
"With fifty thousand Russian troops poised to invade a NATO nation, can Jack Ryan move swiftly enough to stop [Russian president Valeri] Volodin's grand plan of global conflict and conquest?"--Book jacket.